Effect of Periodontal Therapy With Amoxicillin–Metronidazole on Pharyngeal Carriage of Penicillin‐ and Erythromycin‐Resistant Viridans Streptococci. Issue 5 (1st May 2016) - Mombelli, Andrea; Cionca, Norbert; Almaghlouth, Adnan; Cherkaoui, Abdessalam; Schrenzel, Jacques; Giannopoulou, Catherine
Abstract : Background: Previous studies have focused on antibiotic resistance of Gram‐negative bacteria before and after periodontal therapy. The purpose of this analysis is to assess changes in resistance patterns of the commensal Gram‐positive microbiota. The viridans group streptococci (VGS) have been suggested to serve as reservoirs of resistance genes for more pathogenic streptococci and may be implicated in some non‐oral infections. Methods: In this randomized clinical trial, 80 patients with periodontitis are distributed randomly into two groups. In group A, patients received 375 mg amoxicillin and 500 mg metronidazole three times per day for 7 days during the non‐surgical treatment phase (T1). In group B, the antibiotics were administered during the surgical phase (T2). Resistance of VGS to penicillin and erythromycin was determined by the epsilometer test. Results: At baseline, VGS from 12.5% (group A) and 11.8% (group B) of patients had a minimum inhibitory concentration (MIC) >2 μg/mL to penicillin. Three months after T1, VGS from 15.6% and 16.7% of patients had an MIC >2 μg/mL, respectively. Six months after T2 VGS from 5.9% and 5.9% and 12 months after T2 VGS from 6.1% and 6.3% patients had an MIC >2 μg/mL. There was no effect of therapy with antibiotics, administered either in T1 or T2, on the carriage of penicillin‐resistant VGS. Erythromycin resistance was high at baseline and remained unchanged throughout the study. MICs for penicillin and erythromycin were correlated ( P <0.05). Conclusion: Amoxicillin plus metronidazole did not significantly affect the resistance pattern of the VGS to penicillin or erythromycin.